Terracottas of Bengal : an analytical study (with 276 illustration) - Haque, Zulekha, 1938- (Studies in Bengal art series ;, 2014)
On terracotta plaques in the archaeological sites found both in East and West Bengal. Studied in the context of history, society and its peoples.